TOURISM VILLAGE DEVELOPMENT STRATEGY BY GUNUNGSARI VILLAGE GOVERNMENT SADANANYA DISTRICT CIAMIS DISTRICT - Enjang Abdul Rouf; Endah Vestikowati; Irfan Nursetiawan (Faculty of Social and Political Science Universitas Galuh, 2023)
This research is motivated by the results of observations which show that the tourism village development strategy by the Gunungsari Village government, Sadananya District, Ciamis Regency is still not optimal. The purpose of this study was to determine the tourism village development strategy by the Gunungsari Village Government, Sadananya District, Ciamis Regency. The method used in this research is descriptive analysis. There are 7 informants. Data collection techniques are library research, field studies (observations and interviews) and documentation. The author uses qualitative data analysis techniques through processing data from interviews and observations to draw conclusions so that they can answer the problems in the study. Based on the results of the study, it is known that: the tourism village development strategy by the village government is not optimal, this is because the village government has not implemented according to the four levels of strategy, this is evidenced by the lack of facilities and infrastructure in tourist villages such as insufficient parking space so that visitors use their shoulders. the road in parking their vehicles in addition to the lack of trash cans so that visitors litter. The promotion system is still lacking in addition to the lack of cooperation with local governments in promoting tourism objects. This is due to the lack of village government in providing guidance and training in the development of tourist villages. Lack of opportunities for local communities to market their work. This is because there is no place to sell the work provided by the village government for the community and there has not been a collection of community works that can be used as souvenirs for visitors who come. Therefore, various efforts have been made, such as maintaining the environment around the tourist village on a regular basis. Adding various facilities and infrastructure that are still lacking and maximizing accessibility and accommodation in tourist villages so that it can make it easier for visitors to come and stay for long at tourist objects and empower local communities by holding business skills training activities so that people can take advantage of existing potential in increasing people's income.